Framing Men's Experience in the Procreative Realm. (August 2013) - Marsiglio, William; Lohan, Maria; Culley, Lorraine
Informed by a critical men's studies perspective, as well as symbolic interactionist and life course themes, we explore how men's relationship to the procreative realm is currently conceptualized in academic scholarship and public policy debates. We articulate opportunities to advance our conceptual understanding of men's experiences with pregnancy and family planning by framing the procreative period as a multilayered, dynamic process. We also delineate a broader agenda for critical research on men's participation in reproductive planning. In particular, we advocate that future research be guided by four strategies: comparative designs, diverse methodologies, prospective and retrospective longitudinal studies, and approaches that capture the multiple, interrelated layers of social life that affect men's thoughts, feelings, and practices in the procreative realm.